Reassessing the impact of social media on healthcare delivery: insights from a less digitalized economy - Emmanuel Bruce; Zhao Shurong; John Amoah; Sulemana Bankuoru Egala; Francis Kofi Sobre Frimpong (Taylor & Francis Group, 2024)
AbstractSocial media plays a crucial role in modern healthcare by promoting patient engagement, facilitating communication among professionals, and serving as a platform for health education and outreach. Its significance in healthcare delivery continues to grow as digital communication becomes increasingly integral to the industry's efforts to improve healthcare outcomes. Nonetheless, existing studies have not adequately and empirically explored its impact in less digitalized economies. Thus, this study seeks to investigate the impact of social media on healthcare delivery systems in a less digitalized economic context. Leveraging the social media engagement theory, the study employs a partial least squares (PLS-SEM) approach to explore the impact of social media in Ghana's healthcare system. Based on a purposely selected sample of 457 healthcare professionals from Ghana, the study found that using social media for crisis management, patient-doctor relationships, and information dissemination positively impacts healthcare systems. On the contrary, social media use for public relations activities did not have any significant impact on healthcare delivery. This study contributes to the growing literature on the affordances of social media in the circular economy towards improved healthcare delivery in emerging economies. The study offers a strategy for optimizing the use of social media within healthcare settings to foster enhanced healthcare outcomes, particularly a less digitalized economies.